Analisis kandungan glukosa dan daya terima gula cair berbahan dasar Ubi Cilembu (Ipomoea batatas L.) - Auliya Zukhruf A'la Choir; Abdul Azis Akbar (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Diabetes prevention can be pursued by utilizing abundant local food. Cilembu sweet potato is a staple food in demand by the community because it has a distinctive sweet taste. The higher starch content than other sweet potatoes makes Cilembu sweet potato a potential starch source, namely into liquid sugar with enzyme hydrolysis. Liquid sugar has advantages over crystal sugar; it dissolves easily during processing and is more practical. Cilembu sweet potato liquid sugar can be used as an alternative to prevent the occurrence of Diabetes Mellitus. Objectives: This study aims to determine glucose levels and acceptability of Cilembu sweet potato liquid sugar (Ipomoea batatas L.) by adding α-amylase and glucoamylase 1, 2, and 3 mL enzymes.Methods: This study used a quasi-experimental design using a Completely Randomized Design (CRD). This study consisted of 3 treatments and 3 replications, adding 1 ml, 2 ml and 3 ml of α-amylase and glucoamylase enzymes. The research on glucose levels was located at the Food Analysis Laboratory of the Jember State Polytechnic, and the acceptance test was carried out at the Faculty of Public Health, University of Jember, on 30 people aged 18-25 years. Glucose levels were tested using the Luff school method. Analysis of glucose level data used the One-Way ANOVA test, while the acceptance test used the Kruskal Wallis test.Results: The results of this study indicate that the lowest average test value for glucose levels in liquid sugar made from Cilembu sweet potato is with the proportion of adding 1 ml amylase enzyme, namely 31,55% with statistical test results p=0,000 with α=0,05. In the acceptability test, which included scent, texture, and taste, the highest score was found in liquid sugar with the addition of 1 ml of the enzyme with statistical test results p=0,012; p=0,014; p=0,000, while the color acceptability had the highest value in liquid sugar with the addition of 2 ml of the enzyme (p=0,004).Conclusion: The best formulation based on the glucose content and acceptability test is liquid sugar with adding 1 ml of enzyme.